The π-Circuit Technique in Coronary Surgery: Analysis of 1359 Consecutive Cases. (August 2019) - Prapas, Sotirios N; Pangiotopoulos, Ioannis A; Leivaditis, Vasileios N; Katsavrias, Konstantinos P; Prapa, Vasiliki S; Linardakis, Ioannis N; Koletsis, Efstratios N; Grapatsas, Konstantinos
Coronary artery bypass surgery still has its unique role in the treatment of coronary artery disease. It faces, however, the continuous challenge of becoming even less invasive and more effective as cases become more complex. We here present the results of 1359 cases treated with the π-circuit technique which consists of an off-pump total myocardial revascularization using composite arterial grafts. The results demonstrate that it is a safe technique providing low mortality, stroke, renal failure, wound infection, and other complication rates. We suggest the application of this technique, as well as of other similar techniques regarding similar principles, especially in high-risk patients.